2021
DOI: 10.1007/s13304-021-01045-z
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic splenectomy as a definitive management option for high-grade traumatic splenic injury when non operative management is not feasible or failed: a 5-year experience from a level one trauma center with minimally invasive surgery expertise

Abstract: Technique, indications and outcomes of laparoscopic splenectomy in stable trauma patients have not been well described yet. All hemodynamically non-compromised abdominal trauma patients who underwent splenectomy from 1/2013 to 12/2017 at our Level 1 trauma center were included. Demographic and clinical data were collected and analysed with per-protocol and an intention-to-treat comparison between open vs laparoscopic groups. 49 splenectomies were performed (16 laparoscopic, 33 open). Among the laparoscopic gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 46 publications
1
17
0
1
Order By: Relevance
“…Meta-analysis results suggested that the length of stay of patients who underwent laparoscopy was significantly shorter than those who underwent laparotomy [MD −3.83, 95% CI (−5.04, −2.62) days, p < 0.00001], there was high heterogeneity (I2 = 98%; see Figure 6A). Eight (7,18,28,31,32,36,37,39) of the ten remaining studies whose data was not suitable for quantitative synthesis were consistent with the above results, while the findings of two studies (19,21) did not favor the above results.…”
Section: Length Of Staysupporting
confidence: 66%
See 3 more Smart Citations
“…Meta-analysis results suggested that the length of stay of patients who underwent laparoscopy was significantly shorter than those who underwent laparotomy [MD −3.83, 95% CI (−5.04, −2.62) days, p < 0.00001], there was high heterogeneity (I2 = 98%; see Figure 6A). Eight (7,18,28,31,32,36,37,39) of the ten remaining studies whose data was not suitable for quantitative synthesis were consistent with the above results, while the findings of two studies (19,21) did not favor the above results.…”
Section: Length Of Staysupporting
confidence: 66%
“…The literature search initially identified 1, 358 papers, of which 41 studies were eligible for the full-text screening process, and 23 studies (7,8,12,(17)(18)(19)(20)(21)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41) were included in the metaanalysis. The PRISMA flow diagram is illustrated in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although laparoscopic splenectomy for non-trauma conditions is quite common, for trauma, it is not norm. However, the TraumaLap Study Group has shown that laparoscopy for splenic injury is useful in the diagnosis of associated injuries concomitant with the splenic injury and may be the definitive management of high-grade splenic injuries which have failed non-operative management, with the potential for fewer adverse post-operative events [ 29 , 30 ]. Certainly, trauma surgeons should consider laparoscopy as an operative option.…”
Section: Discussionmentioning
confidence: 99%